2010
DOI: 10.1097/aud.0b013e3181c12383
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral and Unilateral Cochlear Implant Users Compared on Speech Perception in Noise

Abstract: Objective Compare speech performance in noise with matched bilateral (CICI) and unilateral (CI-Only) cochlear implant users. Design Thirty CICI and 30 CI-Only subjects were tested on a battery of speech perception tests in noise that utilize an 8-loudspeaker array. Results On average, CICI subject's performance with speech in noise was significantly better than the CI-Only subjects. Conclusion The CICI group showed significantly better performance on speech perception in noise compared to the CI-Only sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 7 publications
(7 reference statements)
5
55
1
2
Order By: Relevance
“…2 and 5). These results from retrospective data confirmed that binaural listening provides better outcome than listening monaurally with one CI (Most et al 2012), especially in noise (Ching et al 2004;Ricketts et al 2006;Dunn et al 2010). It was also confirmed that the benefit of binaural listening compared with one CI alone was greater with a second CI than with an HA on average , especially in noise in the present study (+6% for the CI/HA group versus +11% for the CI/ CI group in quiet, and +9% for the CI/HA group versus +16% for the CI/CI group in noise).…”
Section: Bimodal Versus Bilateral: Slight But Significant Advantage Osupporting
confidence: 73%
“…2 and 5). These results from retrospective data confirmed that binaural listening provides better outcome than listening monaurally with one CI (Most et al 2012), especially in noise (Ching et al 2004;Ricketts et al 2006;Dunn et al 2010). It was also confirmed that the benefit of binaural listening compared with one CI alone was greater with a second CI than with an HA on average , especially in noise in the present study (+6% for the CI/HA group versus +11% for the CI/ CI group in quiet, and +9% for the CI/HA group versus +16% for the CI/CI group in noise).…”
Section: Bimodal Versus Bilateral: Slight But Significant Advantage Osupporting
confidence: 73%
“…We identified 15 studies (published in 19 articles) assessing communication-related health outcomes in patients who received bilateral cochlear implants simultaneously, [28][29][30][31][32][33][34][35][36] sequentially, 21,[37][38][39][40][41][42][43] or both 44,45 ( Table 2). All but 2 studies 28,33 of simultaneous bilateral implantation showed a statistically significant improvement in communication-related outcome scores compared with unilateral implantation; in most studies, unilateral implantation was tested by temporarily deactivating 1 implant.…”
Section: Communication-related Outcomes In Bilateral Implantationmentioning
confidence: 99%
“…Bilateral cochlear implants (CIs) can improve speech understanding in noisy environments as well as improve sound localization (Dunn et al, 2010;van Hoesel, 2004;Litovsky et al, 2012). Patients with bilateral CIs receive some of the benefits that come with binaural hearing, but they often still have difficulty with binaural fusion, i.e., fusing sounds from the two ears together into a unitary percept .…”
Section: Introductionmentioning
confidence: 99%